Determinants of German FDI: New Evidence from Micro-Data - Farid Toubal; Jörn Kleinert; Claudia M. Buch (Deutsche Bundesbank, 2003)
This paper provides new evidence on the foreign direct investment stocks of German firms. We use firm-level data for the years 1990-2000 to describe the regional and sectoral patterns of German FDI through gravity-type equations. We provide evidence on the patterns of FDI by sector, by size of the foreign affiliate, and by the number of affiliates per host country. While market size and geographic distance have a significant impact on FDI stocks, we also find differences in the determinants of FDI between sectors as well as between the size of foreign affiliates and the number of foreign affiliates. – – Dieses Papier untersucht die Direktinvestitionsbestände deutscher multinationaler Unternehmen im Ausland auf drei verschiedenen Aggregationsniveaus. Dafür nutzen wir einen reichhaltigen Datensatz auf Unternehmensebene, der sektoral und auf Länderebene aggregiert und als Mikrodatensatz analysiert wird. Unsere Analyse bezieht sich auf die Jahre 1990 bis 2000. Mittels eines Gravitätsansatzes beschreiben wir die sektoralen und regionalen Muster deutscher Direktinvestitionen im Ausland und diskutieren die Unterschiede, die sich für die verschiedenen Aggregationsniveaus ergeben.
Keywords: F0; F21; 330; distance coefficients; gravity equations; foreign direct investment; Direktinvestition; Deutsch; Multinationales Unternehmen; Gravitationsmodell; Branche; Auslandsniederlassung; Betriebsgröße; Schätzung; Deutschland